2023
DOI: 10.3389/fimmu.2023.1113212
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel immune landscape signature as effective diagnostic markers related to immune cell infiltration in diabetic nephropathy

Abstract: BackgroundThe study aimed to identify core biomarkers related to diagnosis and immune microenvironment regulation and explore the immune molecular mechanism of diabetic nephropathy (DN) through bioinformatics analysis.MethodsGSE30529, GSE99325, and GSE104954 were merged with removing batch effects, and different expression genes (DEGs) were screened at a criterion |log2FC| >0.5 and adjusted P <0.05. KEGG, GO, and GSEA analyses were performed. Hub genes were screened by conducting PPI networks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…CX3CR1 is upregulated in diabetic kidneys, and in streptozotocin-induced mouse models of diabetes, CX3CR1 deficiency reduces extracellular matrix deposition, which in turn affects the expression of CCL2. [ 22 ] A and activation of Smad2/3 in the glomeruli of diabetic mice, thereby alleviating proteinuria and podocyte loss in diabetic kidneys. Studies have shown that the early stage of glomerular growth in diabetic rats is accompanied by an increase in the expression of proto-oncogenes c-fos and c-jun [ 23 ] ; Meanwhile, the peroxisome proliferator-activating receptor γ-activating compound thiazolidinedione prevents the activation of the high glucose-induced TGF-1 gene by interacting with the activated protein kinase Cc-Fos-TGF-1 promoter cascade in mesangial cells (MCs) [ 24 , 25 ] ; The study found that CXCL10 reduced collagen production by renal fibroblasts in response to high glucose and TGF-|A, suggesting that CXCL10 can inhibit downstream signaling of the TGF-|A receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CX3CR1 is upregulated in diabetic kidneys, and in streptozotocin-induced mouse models of diabetes, CX3CR1 deficiency reduces extracellular matrix deposition, which in turn affects the expression of CCL2. [ 22 ] A and activation of Smad2/3 in the glomeruli of diabetic mice, thereby alleviating proteinuria and podocyte loss in diabetic kidneys. Studies have shown that the early stage of glomerular growth in diabetic rats is accompanied by an increase in the expression of proto-oncogenes c-fos and c-jun [ 23 ] ; Meanwhile, the peroxisome proliferator-activating receptor γ-activating compound thiazolidinedione prevents the activation of the high glucose-induced TGF-1 gene by interacting with the activated protein kinase Cc-Fos-TGF-1 promoter cascade in mesangial cells (MCs) [ 24 , 25 ] ; The study found that CXCL10 reduced collagen production by renal fibroblasts in response to high glucose and TGF-|A, suggesting that CXCL10 can inhibit downstream signaling of the TGF-|A receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MCP-1/CCR2 axis induces chemotaxis and activation of inflammatory cells and initiates a series of signaling cascades in renal fibrosis ( 25 ). It mediates and promotes renal fibrosis by recruiting monocytes and promotes the activation and transdifferentiation of macrophages ( 26 ). The rationale for targeting MCP-1/CCR2 to treat human related diseases is to use drugs to block MCP-1 or CCR2 and inhibit the activation and conduction of the MCP-1/CCR2 axis, thereby reducing inflammatory cells and proinflammatory cytokines.…”
Section: Mcp-1/ccr2 Signaling Axis and Functional Architecturementioning
confidence: 99%
“…The significance of DGKH and POLR2B in DKD requires further validation. Handi Zhou et al 143 identified CCR2, CX3CR1, and SELP as potential diagnostic biomarkers for DKD, which were associated with checkpoints, cytolytic activity, macrophages, MHC class I molecules, and paraneoplastic inflammation.…”
Section: Bioinformatics Analysis Of Immune Cells In Dkdmentioning
confidence: 99%
“…The significance of DGKH and POLR2B in DKD requires further validation. Handi Zhou et al 143 Although bioinformatics analyses have yielded various results, small sample sizes and database limitations mean that the findings often require validation using basic experimental methods.…”
Section: Bioinformatics Analysis Of Immune Cells In Dkdmentioning
confidence: 99%